A comparison of CT lung voxel density analysis in a blast and non blast injured casualty. Issue 3 (3rd October 2018) - Bourn, Sebastian; E Scott, T; J Hulse, E
Abstract : Introduction: Primary blast lung injury (PBLI) is a prominent feature in casualties following exposure to blast. PBLI carries high morbidity and mortality, but remains difficult to diagnose and quantify. Radiographic diagnosis of PBLI was historically made with the aid of plain radiographs; more recently, qualitative review of CT images has assisted diagnosis. Methods: We report a novel way of measuring post-traumatic acute lung injury using CT lung density analysis in two casualties. One casualty presented following blast exposure with confirmed blast lung injury and the other presented following extremity injury without blast exposure. Three-dimensional lung maps of each casualty were produced from their original trauma CT scan. Analysis of the lung maps allowed quantitative radiological comparison exposing areas of reduced aeration of the patient's lungs. Results: 45% of the blast-exposed lungs were non-aerated compared with 10% in the non-blast-exposed lungs. Discussion: In these example cases quantitative CT lung density analysis allowed blast-injured lungs to be distinguished from non-blast-exposed lungs.